Impact of regional trade agreements on export efficiency – A case study of India - Leena A. Kaushal (Cogent Economics & Finance, 2022)
The study analyses the role of RTAs in determining the export efficiency of India using a stochastic frontier version of the gravity model. We estimate the impact of select RTAs (bilateral, SAFTA, APTA, ASEAN, and MERCOSUR trade bloc) and the partner nation's regulatory quality on India's export efficiency throughout 2008-2018. The findings suggest that India has been substantially able to exploit exports efficiency to its trading partners under FTAs (ASEAN&SAFTA) and bilateral agreements compared to PTAs (MERCOSER&APTA); however, India's exports are yet quite far from the potential frontier. Excluding APTA, all other agreements are statistically significant, implying that joining trade agreements augments India's export efficiency. The study finds that the regulatory quality of importing nations bears a significant positive impact on India's export efficiency. This highlights the importance of good institutions and better regulatory quality in realizing the potential level of exports with partner nations.
Keywords: 330; India; Free trade; FTA; Regional trade; export efficiency; gravity model; stochastic frontier model